2022
DOI: 10.3390/ma15155244
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Electron Beam and the Choice of Heating Membrane on the Evolution of Si Nanowires’ Morphology in In Situ TEM

Abstract: We used in situ transmission electron microscopy (TEM) to observe the dynamic changes of Si nanowires under electron beam irradiation. We found evidence of structural evolutions under TEM observation due to a combination of electron beam and thermal effects. Two types of heating holders were used: a carbon membrane, and a silicon nitride membrane. Different evolution of Si nanowires on these membranes was observed. Regarding the heating of Si nanowires on a C membrane at 800 °C and above, a serious degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Subsequently, the pressure was increased to 150 Pa, and SiH 4 (10 sccm) and H 2 (200 sccm) were introduced while applying 10 W of RF power for 10 min, facilitating the VLS growth of Si nanowires. Note here that Si NWs in this work have structures of crystalline Si cores covered by amorphous Si shells [46]. Following NW synthesis, ultrasonic oscillation in pure water, PBS solution, or absolute ethanol as selected carriers, efficiently detached the Si NWs and enabled their transfer to the suspension medium.…”
Section: Synthesis and Transfer Of Si Nwsmentioning
confidence: 99%
“…Subsequently, the pressure was increased to 150 Pa, and SiH 4 (10 sccm) and H 2 (200 sccm) were introduced while applying 10 W of RF power for 10 min, facilitating the VLS growth of Si nanowires. Note here that Si NWs in this work have structures of crystalline Si cores covered by amorphous Si shells [46]. Following NW synthesis, ultrasonic oscillation in pure water, PBS solution, or absolute ethanol as selected carriers, efficiently detached the Si NWs and enabled their transfer to the suspension medium.…”
Section: Synthesis and Transfer Of Si Nwsmentioning
confidence: 99%
“…It has been proven that an electron beam is a versatile tool for performing alterations into glass (Musterman, et al, 2022). In addition, in situ TEM is most widely used technique due to its various characteristics, and due to the fact that in situ TEM is enthusiastic by observing the real-time material modification, the effect of the e-beam cannot be neglected (Shen, et al, 2022). The experiment of shape alteration has been performed by reducing the diameter of the e-beam in such a way that covering the entire glass fragment.…”
Section: A Shape Alteration Due To E-beam Irradiationmentioning
confidence: 99%
“…Glass formers such as silica and boric oxide, glass modifiers such as soda and lithium oxide, and intermediates such as Al 2 O 3 . Changes due to radiation of glass with a highenergy particle include for instance the modifications in the external shapes of the glass, in particular, changing the external parts of the glass fragment (Gedeon, et al, 2007;Zheng, et al, 2010) and other amorphous materials (Shen, et al, 2022), phase separation (Chen, et al, 2015;DeNatale, et al, 1986;Sun, et al, 2004), ion migration (Yoshida and Tanaka, 1997;Jbara, et al, 1995;Gedeon, et al, 1999), phase alteration (Liu, et al, 2004), the production of bubbles (Leay and Harrison, 2019), which was considered to be oxygen, nanoprecipitation (Qiu, et al, 2002), crystallization (Klimenkov, et al, 2001;Jencic, et al, 1995), hole drilling (Furuya, 2008), and quasi-melting (Ajayan and Ijima, 1992;Ajayan and Marks, 1989;Marks, et al, 1986). Most of these changes were frequently reported in oxide glasses (Skuja, et al, 2005), while the phenomenon of shape transformations was rarely reported (Li, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%